The simulation-based prediction of pipeline inspection data employing the extreme value theory - 338581 Norhazilan Md. Noor; Wolfram, J.; Nordin Yahaya; Asia Pacific Structural Engineering and Construction Conference (5th : 2003 : Johor) (Skudai : Universiti Teknologi Malaysia, 2003)
09